1993
DOI: 10.1136/thx.48.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Body weight and weight gain related to pulmonary function decline in adults: a six year follow up study.

Abstract: Background-Obesity increases the risk of cardiovascular disease, hypertension, diabetes, digestive diseases, and some cancers. Several studies have shown that excess weight or weight gain is related to pulmonary dysfunction, but this issue needs to be further clarified. Methods-The analysis was based on data of the Humboldt cohort study which was conducted in the town of Humboldt, Saskatchewan, Canada. The baseline survey in 1977 included 1202 adults, comprising 94% of all residents aged 25-59 years. Of these,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
116
3
8

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(143 citation statements)
references
References 25 publications
14
116
3
8
Order By: Relevance
“…1,5 ± 11 In the two studies with both men and women, signi®cantly higher effects were found in men. 5,7 Age and height may also be important factors in this relationship, as Bande and colleagues 10 showed that within their younger (mean age 20 y) and taller subjects, changes in weight tended to increase FVC and FEV 1 while the effect was reversed in older and shorter subjects. However, in the Normative Ageing Study, larger effects of weight gain on FVC decrease were found in younger subjects.…”
Section: Changes In Weight Vs Changes In Fevmentioning
confidence: 99%
“…1,5 ± 11 In the two studies with both men and women, signi®cantly higher effects were found in men. 5,7 Age and height may also be important factors in this relationship, as Bande and colleagues 10 showed that within their younger (mean age 20 y) and taller subjects, changes in weight tended to increase FVC and FEV 1 while the effect was reversed in older and shorter subjects. However, in the Normative Ageing Study, larger effects of weight gain on FVC decrease were found in younger subjects.…”
Section: Changes In Weight Vs Changes In Fevmentioning
confidence: 99%
“…In our cross-sectional study, an increase in BMI was also associated with a reduction in FEV 1 /FVC (4). Several longitudinal studies in able-bodied individuals have demonstrated an inverse relationship between BMI or weight gain and pulmonary function (27)(28)(29)(30). Lazarus and colleagues (31) found that both obesity itself and the pattern of body fat distribution had independent effects on ventilatory function, and a central pattern of fat distribution was associated with lower values of FEV 1 and FVC after adjusting for BMI.…”
Section: Discussionmentioning
confidence: 99%
“…There are abundant data showing the relationship between weight (weight gain or weight loss) and lung function [15][16][17][18][19] . In principle, it seems logical to take changes in weight into account to predict various lung function indices.…”
Section: Discussionmentioning
confidence: 99%